2018
DOI: 10.1111/tid.12996
|View full text |Cite
|
Sign up to set email alerts
|

Reactivation of Chagas disease among heart transplant recipients in the United States, 2012‐2016

Abstract: Transplant programs in the United States are encouraged to implement a monitoring program for heart transplant recipients with Chagas disease. Our experience using a preemptive approach of monitoring for Chagas disease reactivation was effective at identifying reactivation before symptoms developed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
57
0
5

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(64 citation statements)
references
References 37 publications
2
57
0
5
Order By: Relevance
“…A recent study conducted in the United States between 2012-2016 showed a rate of reactivation of 61% among patients undergoing HTx [45]. In another study from the USA, the rate of reactivation after HTx was 45.5% [46]. The 10-year survival rate of patients with HTx for CHC in the USA study was 57% and did not differ from the reported survival rate of patients with idiopathic dilated cardiomyopathy [48].…”
Section: Risk Of Reactivation In Infected Recipientsmentioning
confidence: 68%
See 1 more Smart Citation
“…A recent study conducted in the United States between 2012-2016 showed a rate of reactivation of 61% among patients undergoing HTx [45]. In another study from the USA, the rate of reactivation after HTx was 45.5% [46]. The 10-year survival rate of patients with HTx for CHC in the USA study was 57% and did not differ from the reported survival rate of patients with idiopathic dilated cardiomyopathy [48].…”
Section: Risk Of Reactivation In Infected Recipientsmentioning
confidence: 68%
“…Risk of reactivation of T. cruzi infection varies according to the organ transplanted and the degree of drug immunosuppression, with the highest risk associated with heart transplantation (mean average of 44.9%) and similar risk for kidney (21.7%) and liver (33.3%) transplantation, as shown in Table 2 [30,[33][34][35][36][37][38][39][40][41][42][43][44][45][46][47]. The majority of the studies regarding reactivation came from Brazil and are related to patients who undergo heart transplantation, with a prevalence rate ranging from 23% to 90% [33][34][35][36][37][38][39][40][41]44].…”
Section: Risk Of Reactivation In Infected Recipientsmentioning
confidence: 99%
“…There is consensus the best way to control CDR is a close follow‐up of the transplanted patient, not prophylactic treatment. Besides the careful search for parasites in EMB, monitoring for CDR is based on microscopic examination of blood smears and fresh buffy coat preparations, and more recently blood PCR for T cruzi DNA . As non‐immunosupressed, chronic chagasic patients can show positive PCR in the blood, probably due to parasite persistence and fortuitous blood circulation, one proposed criterion for the diagnoses of CDR is sequential positive blood PCR results (at least two) of increasing parasitic load …”
Section: Discussionmentioning
confidence: 99%
“…Besides the careful search for parasites in EMB, monitoring for CDR is based on microscopic examination of blood smears and fresh buffy coat preparations, and more recently blood PCR for T cruzi DNA. 5,9,16,17 As non-immunosupressed, chronic chagasic patients can show positive PCR in the blood, 18 probably due to parasite persistence and fortuitous blood circulation, one proposed criterion for the diagnoses of CDR is sequential positive blood PCR results (at least two) of increasing parasitic load. 17 In this study, we showed sequential measurement of T cruzi parasitic load in EMB is useful for the early detection and treatment follow-up of CDR.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation